2022
DOI: 10.1101/2022.05.28.493826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physiological Characteristics of Bacterial Droplets Indicate a Catastrophic Consequence With an Increase in Impact Velocity

Abstract: Droplet impacts on various surfaces play a profound role in different bio-physiological processes and engineering applications. The current study opens a new realm that investigates the plausible effect of impact velocities on bacteria-laden droplets against a solid surface. We unveiled the alarming consequences of Salmonella Typhimurium (STM) laden drop, carrying out the in vitro and intracellular viability of STM to the impact Weber numbers ranging from 100-750. The specified Weber number range mimics the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This difference is significant in straight channel compared to serpentine channels. Similar trends have been previously reported by our group for Salmonella Typhimurium subjected to mechanical stresses 68 . Ares et al 78 reported the importance of cholesterol in reducing the anti-phagocytic properties of KP capsules.…”
Section: Intracellular Proliferation Of Bacterial Cells In Raw2647 Ma...supporting
confidence: 92%
“…This difference is significant in straight channel compared to serpentine channels. Similar trends have been previously reported by our group for Salmonella Typhimurium subjected to mechanical stresses 68 . Ares et al 78 reported the importance of cholesterol in reducing the anti-phagocytic properties of KP capsules.…”
Section: Intracellular Proliferation Of Bacterial Cells In Raw2647 Ma...supporting
confidence: 92%
“…67 Interestingly, there can be bacteria that are alive but not culturable. 68 It has been shown that various stress conditions like osmotic stress, 69 thermal stress, 69 oxidative stress, 70 shear stress, 71 evaporative and impact stress 72 result in a loss of viability of the bacterial population. We conduct different tests by maintaining the flow rate and geometry constant in each one of them to understand how the viability of bacterial cells changes.…”
Section: Viability Assaymentioning
confidence: 99%
“…Upon impact, the kinetic energy can create substantial mechanical stresses inside the microbial droplet as it spreads. 28 However, the time scale of the mechanical stresses developed inside the microbial droplet is typically in the range of milliseconds. Our study, however, reveals that this millisecond time scale plays a central role in determining the outcome of the bacterial-surface interactions.…”
Section: Introductionmentioning
confidence: 99%